PENGEMBANGAN CYBERBOARD UNTUK MENINGKATKAN PEMAHAMAN CYBER SECURITY SISWA PADA MATA PELAJARAN INFORMATIKA - Mawaddah, Addina Nurul; Rosyida, Fatiya; Hidayatullah, M Syarif (Jurnal Inovasi dan Teknologi Pendidikan, 2025)
Junior high school students' understanding of cybersecurity concepts remains relatively low due to the lack of interactive learning media tailored to students’ characteristics. This study aims to develop CyberBoard, an educational board game designed to enhance eighth-grade students' understanding of basic cybersecurity concepts. The research was conducted following the initial stages of the Research and Development (R&D) method, employing the ADDIE model (Analysis, Design, Development, Implementation, and Evaluation) as the approach for designing and implementing the learning media. The results showed an improvement in students’ average scores from 68.81 (pretest) to 84.52 (posttest). The normality test indicated that the data were normally distributed (p > 0.05), and the N-Gain test resulted in a score of 0.6818 or 68.18%, which falls into the "moderately effective" category. Therefore, it can be concluded that CyberBoard is effective in improving students’ understanding of cybersecurity.